Manajemen strategis pengelolaan ekspor jasa tenaga kerja Indonesia (Studi pada Direktorat Jasa Tenaga Kerja Luar Negeri) - ISWANDI, Henry (Universitas Gadjah Mada, 1998)
The national program of TKI (Indonesian Work Force) exports to overseas is a strategical means in the effort to overcome the unemployment problems in our country. In the last Pelita V, numkrs of TKI employed overseas were 652.272 people which had given foreign incomes of US $.1.223.431.455, and whenever viewed from economical aspect, it was the second non-petroleum exports to the tourism. In spite the quantities of TKI exports was continually increased, it has not yet been answered the entire problems faced. The TKIas a potential form of SDM (human resources) in the implementation of development should not merely viewed to be a comoddity, the competencial aspect of TKI consisting economical values in the production process have to be proportionally treatened in the context of human existence as a whole. It is the uniqueness of this program that have given the opportunities for appearance of structural problem excesses such as ilegally delivering of TKI, unsufficiently protection for TKI,the visa abusements, over stay, falsifjmg of TKI age, the problems of Indonesian citizen in the overseas, and various other insulation forms. Because of many related elements in this program management, at least it is requiring the intersectoral integrated coordination efforts supporting by commitment and consistencies in the quality improvement of its implementation. One of these related institutions in this program implementation is Dit. Jasa TKLN,which have been founded based on Kepmenaker No. 28/MEN/1994 with main duty to formulating public policies of government that supporting the implementation of TKI service exports. In addition to reflecting the existential responsibles, the policy formulation is a response to any change occurred in their respective anvironments. In order to give properly responses, it is needed analysis, estimation and prediction of various aspects existing in both external and internal environments of organization. Based on the above reasoning, the study in this thesis was conducted by means of strategical management approach, using analitical tool of SWOT in order to h o w various opportunities and threats faced and various strengths and weaknesses owned. Then, based on these situation, it is hoped that strategical issues can be identified such as: I;?tst, one that related to high public demands for working in the foreign country. Second, one that related to optimalizational efforts of organization functional through utilization of existing SDM potentials. Third, requirement for increasing commitment and consistence from related institutions in the national program implementation of TKI service exports. The strategies implemented, of course, have to be based on matrices of SWOT analysis results, by considering the elements of strengths and weaknesses as well as opportunities and threats existed. From these analysis results, for responding to the first issue, the strategy alternative implemented was to the one that placed on the quadrant I or S 0 Strategies, i.e., using the strengths to capture the existing opportunities, and the to respond to the second issue, the strategy alternative implemented was the one that placed on quadrant 111 or W 0 Strategies, i.e., overcoming the weaknesses by taking the existing opportunities, whereas to respond to third issue, strategy alternative implemented was the one that placed on quadrant I1 or S T Strategies, i.e., using strengths to avoiding the threats.